Effect of family "upward" intergenerational support on the health of rural elderly in China: Evidence from Chinese Longitudinal Healthy Longevity Survey. - Zhan Shu (Public Library of Science (PLoS), 2021)
As health challenging rural elderly in an aging population, more attention is being paid on impact of family intergenerational support on the health of the elderly. This paper investigates the effects of children's intergenerational economic support and non-economic support on physical, mental, and functional health of rural elderly in China in the mean while. This paper applies the 2014 Chinese Longitudinal Healthy Longevity Survey (CLHLS), in particular, applying exploratory factor analysis to ascertain latent variables and Structural Equation Model (SEM), and analyzes the impacts of "Upward" intergenerational support on health of rural elderly. As resulted, after controlling the socioeconomic status of the rural elderly, the family "upward" intergenerational support influences the elderly's physical health at a percentage of 11.7%, mental health 29.8%, and physiological function 12.6%. Moreover, "Upward" economic support has a positive effect on physiological function (P<0.05). "Upward" non-economic support has negative effects on physiological function and mental health (P<0.05), while it has a positive effect on physical health. In addition, economically independent rural elderly are more likely to benefit from the health of "upward" intergenerational support, especially mental health. In particular, those results are robust. "Upward" intergenerational support plays an important role for the health of rural elderly. For the rural elderly of economic independence, to improve the quality of care and spiritual support, it is important to solve the health problems. In addition, it is necessary to build a comprehensive old-age security and support system for family, community, and society jointly to improve the health of the rural elderly.